2009
DOI: 10.1038/ncb1985
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage signalling prevents deleterious telomere addition at DNA breaks

Abstract: The response to DNA damage involves regulation of multiple essential processes to maximize the accuracy of DNA damage repair and cell survival 1. Telomerase has the potential to interfere with repair by inappropriately adding telomeres to DNA breaks. It was unknown whether cells modulate telomerase in response to DNA damage, to increase the accuracy of repair. Here we report that telomerase action is regulated as a part of the cellular response to a DNA double-strand break (DSB). Using yeast, we show that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
147
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(154 citation statements)
references
References 20 publications
(26 reference statements)
4
147
0
Order By: Relevance
“…De novo telomere addition was assayed in SRS2 and srs2 Δ using a previously described genetic test (Makovets & Blackburn, 2009) involving a single galactose‐inducible DSB (Fig 2A). Because de novo telomere addition normally occurs with a very low frequency due to telomerase inhibition by Pif1 (Schulz & Zakian, 1994), the pif1‐m2 background was used in the genetic assay.…”
Section: Resultsmentioning
confidence: 99%
“…De novo telomere addition was assayed in SRS2 and srs2 Δ using a previously described genetic test (Makovets & Blackburn, 2009) involving a single galactose‐inducible DSB (Fig 2A). Because de novo telomere addition normally occurs with a very low frequency due to telomerase inhibition by Pif1 (Schulz & Zakian, 1994), the pif1‐m2 background was used in the genetic assay.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, there was a putative Rad53 binding site. Recently, researchers uncovered a novel MEC1-RAD53-DCN1-dependent signaling pathway that prevented deleterious DSB-specific telomerase additions at DNA breaks, thus preserving genomic integrity (Makovets et al, 2009;Kurz et al, 2008). Taken together, these findings suggested that the DCUN1D5 might play a role in DNA damage response to genotoxic stress and probably subsequent DNA repair.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to prolonged Rad53 activation in postsenescent est2Δ and tlc1Δ survivors, checkpoint activation in presenescent telomerase-deficient est2Δ cells was as short-lived as in wild-type cells ( Figure 2C). Thus, these data indicate that it was the establishment of the ALT pathway, rather than just the loss of telomerase, that was responsible for prolonged checkpoint activation in our survivors.Abolition of the checkpoint response does not restore de novo telomere addition in survivors As indicated above, DNA damage checkpoints inhibit de novo telomere addition at DSBs by telomerase to prevent genome instability (Makovets and Blackburn 2009;Zhang and Durocher 2009). We thus investigated if prolonged checkpoint activation also contributes to impaired de novo telomere addition in postsenescent survivors.…”
mentioning
confidence: 99%
“…Abolition of the checkpoint response does not restore de novo telomere addition in survivors As indicated above, DNA damage checkpoints inhibit de novo telomere addition at DSBs by telomerase to prevent genome instability (Makovets and Blackburn 2009;Zhang and Durocher 2009). We thus investigated if prolonged checkpoint activation also contributes to impaired de novo telomere addition in postsenescent survivors.…”
mentioning
confidence: 99%
See 1 more Smart Citation